The Death and Life of Private Landlordism: How Financialized Homeownership Gave Birth to the Buy-To-Let Market. Issue 5 (20th October 2021) - B. Aalbers, Manuel; Hochstenbach, Cody; Bosma, Jelke; Fernandez, Rodrigo
ABSTRACT: The private rental sector (PRS) is making a surprising comeback. A central argument in our paper is that we see the rise of PRS and the associated stagnation of homeownership as springing from the contradictions inherent to financialized homeowner societies. Rather than a feature of either mature or late homeowner societies, contradictions of the promotion of homeownership through the expansion of mortgage markets paved the way for a revival of the PRS. Our case is the Netherlands, but our argument has a wider remit. We sketch the dominant trends in Dutch housing policy and present an overview of the rise of PRS and Buy-To-Let in Dutch cities. We identify how housing policies and realities have driven a shift from a debt -driven to a wealth -driven model of financialization, in which the demand for PRS as an investment class and as a place to live has become central.